2006
DOI: 10.1007/s11104-006-0055-7
|View full text |Cite
|
Sign up to set email alerts
|

Soil nitrate accumulation, leaching and crop nitrogen use as influenced by fertilization and irrigation in an intensive wheat–maize double cropping system in the North China Plain

Abstract: There is a growing concern about excessive nitrogen (N) and water use in agricultural systems in North China due to the reduced resource use efficiency and increased groundwater pollution. A two-year experiment with two soil moisture by four N treatments was conducted to investigate the effects of N application rates and soil moisture on soil N dynamics, crop yield, N uptake and use efficiency in an intensive wheat-maize double cropping system (wheat-maize rotation) in the North China Plain. Under the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
119
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(137 citation statements)
references
References 12 publications
17
119
0
1
Order By: Relevance
“…This implied that rainfall and irrigation episodes during the first two winter wheat seasons had little effect on water seepage at the 2.0-m soil layer. Field observation and modeling in the NCP also suggested that no leakage occurred even under the recommended amount of irrigation (B75 mm) during the winter wheat season assuming 1-m as the rooting zone (Fan et al 2001;Gong and Li 1995;Yuan et al 1995).…”
Section: Nitrate Nitrogen In Leachatementioning
confidence: 98%
“…This implied that rainfall and irrigation episodes during the first two winter wheat seasons had little effect on water seepage at the 2.0-m soil layer. Field observation and modeling in the NCP also suggested that no leakage occurred even under the recommended amount of irrigation (B75 mm) during the winter wheat season assuming 1-m as the rooting zone (Fan et al 2001;Gong and Li 1995;Yuan et al 1995).…”
Section: Nitrate Nitrogen In Leachatementioning
confidence: 98%
“…N leaching as it was emphasised by Šima et al (2014a) and Šima et al (2014b). Moreover, Fang et al (2006) conducted an experiment with two soil moisture by four N treatments. The study was conducted to investigate the effects of N application doses and soil moisture on soil N dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…The NO 3 -N in the drained solution for all treatment options was higher than NH 4 -N because of the higher solubility and lower affinity of NO 3 -ions for the adsorption sites in the soil. Significant higher (about 1.2 folds) N-(NO 3 -+NH 4 + ), P and K leaching occurred at deeper water table (90±1.5 cm depth) than shallow water table (30±1.5 cm depth) probably due to the higher starting available nutrients in the lower water table (Fang et al, 2006). On the other hand, 42.3, 50.0 and 56.4% losses of N-(NO 3 -+NH 4 + ), P and K, respectively, were recorded with 6 irrigations scheduled for IW: CPE of 0.3; these nutrient losses found maximum as compared to different water table depths and irrigation methods.…”
Section: Growth and Yield Attributesmentioning
confidence: 94%